A device for the local measurement of water evaporation rate. (30th September 2020) - Hall, Christopher; Hamilton, Andrea
Abstract: Evaporation plays a central but largely invisible role in the moisture dynamics of buildings and urban microenvironments. Local evaporation rates control water flux and material damage, and are altered by climate change. While potential evaporation (PE) (or potential evapotranspiration (PET)) can be estimated on the large-scale, there are few if any methods of making local PE measurements. We describe here a simple device ( patch evaporimeter ) for measuring PE at point locations on the surfaces of built structures. The device combines a sintered-quartz disc as a water reservoir and a low-cost remotely-readable humidity sensor to detect the drying time. The patch evaporimeter may be widely useful in monitoring evaporation rates in a variety of microenvironments.